Deficiency of carbohydrate response element-binding protein (ChREBP) reduces lipogenesis as well as glycolysis - Iizuka, Katsumi (National Academy of Sciences, 2004)
The liver provides for long-term energy needs of the body by converting excess carbohydrate into fat for storage. Insulin is one factor that promotes hepatic lipogenesis, but there is increasing evidence that glucose also contributes to the coordinated regulation of carbohydrate and fat metabolism in liver by mechanisms that are independent of insulin. In this study, we show that the transcription factor, carbohydrate response element-binding protein (ChREBP), is required both for basal and carbohydrate-induced expression of several liver enzymes essential for coordinated control of glucose metabolism, fatty acid, and the synthesis of fatty acids and triglycerides in vivo.